Recycled Planet - Anna Claybourne (Franklin Watts, 2022)
The familiar refrain of "recycle, reduce, reuse" has been around for decades. Nonetheless, many people still don't make the effort to follow these principles when disposing of used items or obtaining new ones. This vital volume helps readers understand why recycling is important, how it happens, and the problems that arise during the recycling process. Additionally, it offers age-appropriate solutions readers can begin to implement in their lives and communities right away and long term.
Keywords: Sharing The Planet -- -Waste Management